2011
DOI: 10.1007/s00334-011-0335-x
|View full text |Cite
|
Sign up to set email alerts
|

Do moss samples, pollen traps and modern lake sediments all collect pollen in the same way? A comparison from the forest limit area of northernmost Europe

Abstract: Moss polsters, pollen traps and lake surface sediment samples are commonly used as climate calibration data or as modern analogues for reconstructing vegetation from fossil profiles, but the differences in pollen content between these media have received little attention. This study aims to analyse how the three media differ in reflecting individual vegetation types and spatial differences in vegetation. 119 modern samples (64 moss polsters, 37 lake surface sediment samples and 18 pollen traps from which a col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 33 publications
2
34
0
1
Order By: Relevance
“…It has been noticed earlier (Vermoere et al 2000;Pardoe et al 2010;Lisitsyna et al 2012) that the AP in moss samples achieves higher percentages than in the adjacent traps and, therefore, the investigation of the accumulation of tree pollen, in terms of the growth form of the parent plant, is of interest. The difference in the deposition period length from the median values in the samples estimated by groups: TTP, AP, and shrubs, dwarf shrubs and herbaceous species ( Figure 3A).…”
Section: Differential Retention Of Pollen In Mosses Versus Trapsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noticed earlier (Vermoere et al 2000;Pardoe et al 2010;Lisitsyna et al 2012) that the AP in moss samples achieves higher percentages than in the adjacent traps and, therefore, the investigation of the accumulation of tree pollen, in terms of the growth form of the parent plant, is of interest. The difference in the deposition period length from the median values in the samples estimated by groups: TTP, AP, and shrubs, dwarf shrubs and herbaceous species ( Figure 3A).…”
Section: Differential Retention Of Pollen In Mosses Versus Trapsmentioning
confidence: 99%
“…pollen tetrads of Ericales) might show a similar tendency, but this question has not yet been studied. The diversity of herbaceous pollen types is also lower and arboreal pollen (AP) percentages are higher in moss polsters than in pollen traps (Tonkov et al 2001;Räsänen et al 2004;Lazarova et al 2006;Atanassova 2007;Lisitsyna et al 2012). The origins of such differences have not received sufficient attention; however, they may bias the interpretation of pollen profiles when modern pollen data from only one of the two media are used.…”
mentioning
confidence: 94%
“…Modern pollen assemblages are mainly collected from airborne pollen collectors (e.g., Cour et al, 1999;Giesecke et al, 2010), moss polsters (e.g., Hicks and Birks, 1996;Mazier et al, 2006), topsoils (e.g., Xu et al, 2009;Zhang et al, 2010) and surface lake sediments (e.g., Herzschuh, 2007;Seppa et al, 2004). However, the four types of pollen traps always yield different pollen assemblages even if they are collected from the same site (e.g., Fall, 1992;Wilmshurt and McGlone, 2005a;Lisitsyna et al, 2012;). Consequently, many palynologists (e.g., Seppa et al, 2004;Birks et al, 2010) emphasize that the modern pollen calibration set for quantitatively reconstructing palaeoclimate should be established based on the pollen data from surface lake sediments because most fossil pollen data are extracted from lacustrine sediments (such as lake cores).…”
mentioning
confidence: 99%
“…A comparison of the pollen trapping characteristics of moss polsters, pollen traps and lake sediments showed that they reflected differences in vegetation types in similar ways, but that pollen traps tended to be biased towards lower tree pollen and higher NAP percentages than the other types, and Pinus pollen is captured more effectively by moss polsters than by pollen traps (Lisitsyna et al, 2012). Most work to date has used moss polsters as the pollen trap.…”
Section: Moss Polsters As Pollen Assemblage Trapsmentioning
confidence: 99%